Elemen-Elemen Pengelolaan Keuangan Dalam Islam - Haris, Abdul (Jurnal Manajemen dan Bisnis (JMB), 2025)
Financial management from an Islamic perspective not only focuses on material aspects but also includes spiritual and moral dimensions. This article discusses the main elements of financial management according to Islamic principles, such as the importance of sincere intentions, the prohibition of usury, and the principles of justice, transparency, and balance in spending, earning, and managing wealth. Through a literature review of primary sources such as the Qur'an and hadith, as well as references from scholars and experts in Islamic economics, this article aims to provide a comprehensive understanding of the values underlying Islamic financial management. It is hoped that this understanding can serve as a foundation in building a financial system that is not only efficient but also ethical and socially just in accordance with Islamic teachings